Description of immatures associated with adults of two species of Macrogynoplax Enderlein and one species of Enderleina Jewett (Plecoptera: Perlidae) of the Brazilian Amazon - Ribeiro, José Moacir Ferreira; Gorayeb, Inocêncio De Sousa (Zootaxa, 2015)
Nymphs of Macrogynoplax delicata Ribeiro-Ferreira & Froehlich, 1999, M. pulchra Ribeiro-Ferreira & Froehlich, 1999, and E. froehlichi Ribeiro-Ferreira, 1996 were associated with adults by rearing and described for the first time. The known distribution of each species has been increased.